Implementasi Sistem Informasi E-Commerce Dalam Meningkatkan Penjualan Online - Elsi Novita Sary; Deshy Shilvana (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
E-commerce is a need in the rapidly evolving business world to boost and succeed in both product sales and business rivalry. Buying, selling, and marketing activities are all more productive when e-commerce is used, since it facilitates easier transactions, lowers costs, and expedites the transaction process. Additionally, the quality of data transfer is superior to that of manual processes, which do not perform re-entry and hence provide room for human error. From simple to modern and fast-paced, the dynamics of business competition in the world of information technology development have occasionally affected most people. As a result, it has an effect on information behavior in all fields, including education, health, entertainment, and resources. Information, labor, the business world, and communication without limitations of place or time. The need for faster and cheaper information is undoubtedly prompted by this. The internet can be used to do this.